Analisis Perbandingan Karakteristik Aliran Teradap Nilai Kekasaran Pipa Yang Berbeda - Gaffar, Farida; Kasmawati, Kasmawati; Anwar, Fitria; Almidar, Hesti; Latif, Fauziah (Jurnal Karajata Engineering, 2024)
Flow obstructions often occur in the flow that passes through a pipe installation. As a result, head loss and pressure drop occur which are influenced by fluid friction and changes in the flow pattern of a pipe. However, under certain conditions, frictional resistance is only influenced by fluid viscosity. The aim of this research is to analyze the characteristics of the flow of roughness values ​​in PVC pipes and the flow of roughness values ​​in PP-R pipes using experimental methods carried out in the laboratory. The data that has been collected analyzed using the Reynolds equation, Darcy equation and Bernoulli equation. The research results showed that the characteristic of PVC pipes with the largest froude number value which 0.315 and the smallest which 0.090 were subcritical flow. Meanwhile, the characteristic of the PP-R pipe with the largest froude number value which 0.297 and the smallest which 0.057 were also subcritical flow.